Dampak Maloklusi Terhadap Psikososial Remaja - Asriawal; Saleh, Muh; Baharuddin; Hijriyati Syam, Nur (Media Kesehatan Gigi : Politeknik Kesehatan Makassar, 2025)
Dental and oral health problems in Indonesia remain quite prevalent, with 57% of the population experiencing issues, yet only 10.2% of them receive treatment. One of the most commonly found problems is malocclusion, which refers to the misalignment of teeth and affects around 80% of the population. This condition negatively impacts daily activities, including psychosocial aspects. Previous studies have shown that malocclusion can affect self-confidence and appearance, thereby requiring special attention in orthodontic care.This study is an analytical observational research, in which the researcher directly observes subjects to identify relationships between two or more variables without administering treatment or intervention. The research design used is cross-sectional, which assesses the relationship between independent and dependent variables at a specific point in time without follow-up. The results of the bivariate analysis using the Chi-Square test indicated that there is no significant relationship between malocclusion and psychosocial conditions among adolescents at SMA Negeri 9 Makassar (p = 0.149). Most respondents had Class I malocclusion, commonly in the form of crowding, but due to low levels of knowledge and awareness, they were less conscious of the social impact of their condition. In line with previous findings, this study concludes that malocclusion does not have a significant impact on adolescents’ psychological condition. All adolescents identified with malocclusion at the school were female, who also showed the highest prevalence.